Practical research methods in education an early researcher's critical guide - Lambert, Mike 1950- (Routledge, 2019)
"This insightful book offers detailed illustration of a range of data-collection methods and approaches used in educational research; drawing on the research, practical experiences and reflections of active researchers it is ideal for anyone deciding on the best approach and methodology for their own investigations. Each chapter offers examples, tasks for students to undertake and suggestions for further reading, all designed to strengthen understanding of practical methods of data collection in educational and social-science research. The book is a unique and valuable practical resource for any students interested and engaged in the planning and completion of their own research investigations"--